Solid state fermentation of palm kernel meal by using Aspergillus niger - ., Supriyati; Pasaribu, T; Hamid, H; Sinurat, A.P (Indonesian Animal Sciences Society, 1998)
The solid state fermentation technique on palm kernel meal by using Aspergillus niger wild type and NRRL 337 was studied. The fermentation was carried out at 30oC for 3 days continued with enzymatic process at room temperature and 40oC for 2 days. The result showed that at the third days of fermentation spores started to grow on the surface. The 3rd days fermentation can improve protein content and in vitro digestibility (IVDMD) with minimal loss of dry matter. The dry matter contents at 3 days fermentation were 48.88 and 48.83% for product using Aspergillus niger wild type and NRRL 337. Combination 3 days fermentation and 2 days enzymatic process at room temperature by using Aspergillus niger NRRL 337 type gave the best product with optimal IVDMD value and protein digestibility of 51.47 and 71.33%. Â Key words : Palm kernel meal, fermentation, Aspergillus niger